Pengaruh Model Realistic Mathematic Education Berbantuan Media PhET Simulations terhadap Kemampuan Pemahaman Konsep Matematis Peserta Didik - Maulidawanti, Dwi; Rahayu, Puji; Mustikaati, Wina (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
This study is motivated by the limited mathematical understanding of students regarding concepts related to everyday life, which significantly impacts their ability to grasp mathematical concepts. The objective is to examine the effect of the Realistic Mathematics Education (RME) model supported by PhET Simulations on students’ mathematical concept comprehension, as well as to compare the effectiveness of the RME model assisted by PhET Simulations with the Problem Based Learning (PBL) model. A quantitative method with a quasi-experimental non-equivalent control group design was employed, involving 46 purposively selected students. Data were collected through mathematical concept comprehension tests and analyzed using simple linear regression and N-Gain calculations. The results indicate that the implementation of the RME model supported by PhET Simulations significantly improves students’ mathematical concept comprehension, with higher average gains observed in the experimental class compared to the control class. These findings support the theory that concepts independently constructed by students are more easily retained than those directly presented, and that learning connecting mathematics to real-life contexts makes the material more meaningful and applicable. In conclusion, the RME model assisted by PhET Simulations can serve as an effective alternative learning model to enhance mathematical concept comprehension, especially for second-grade elementary students. The implications of this study contribute to the development of more contextual and meaningful mathematics teaching strategies at the elementary school level.